The effects of technology-mediated immediate feedback on kindergarten students' attitudes, emotions, engagement and learning outcomes during literacy skills development. (August 2015) - Muis, Krista R.; Ranellucci, John; Trevors, Gregory; Duffy, Melissa C.
Abstract: Two studies were conducted to examine kindergarten students' perceptions of technology use in the classroom, and the effects of receiving immediate feedback versus no feedback while using this technology on their attitudes, emotions, engagement, and learning outcomes in the context of literacy skills development. To assess students' perceptions of technology use in the classroom, structured interviews were conducted. Students then used various tablet applications (apps) that provided or did not provide feedback across various literacy tasks. A repeated measures design was used for both studies. In Study 1, 31 students (16 girls) were interviewed and tested over two sessions in April (8th month of school). In Study 2, a new sample of 33 students (16 girls) was interviewed and tested in two sessions in October (2nd month) and again in two sessions in April. Analysis of interviews revealed that students enjoyed receiving positive feedback, but did not like the negative feedback they received when their answers were incorrect. Analyses of quantitative data revealed that, for Study 1, technology-mediated feedback resulted in lower levels of enjoyment but higher levels of achievement compared to when no feedback was provided. For Study 2, technology-mediated feedback resulted in more boredom and less engagement in October compared to when no feedback was given. By April, however, feedback resulted in less boredom and higher levels of achievement compared to no feedback. Theoretical and pedagogical implications are discussed. Highlights: The effect of feedback on students' attitudes, emotions, engagement, and achievement was explored. Two studies were conducted with kindergarten students in the context of literacy development. Students completed a series of literacy tasks with feedback or no feedback. Immediate feedback resulted in higher levels of achievement by the end of the school year.